Regenerasi Ulama: Antara Pesantren Dengan Pendidikan Kader Ulama - Lusinta Rehna Ginting (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2020)
The existence of Islam from time to time in fact cannot be separated from the influence of the scholars who struggle in spreading the religion of Islam to all corners of the world. The struggle (jihad) of the scholars is carried out at the expense of life, property, thoughts and everything that can be fought for in order to spread the religion of Islam. It can be said that the ulama were the spearhead of the spread of Islam in the world after the death of the prophets and apostles of Allah. The presence of scholars from every era provides inspirational stories for human beings. In fact, there are certain times that are so fertile that it gives birth to a generation of qualified scholars in various branches of science. All of that can not be separated from the education taught to the younger generation of Islam either in the context of pesantren or otherwise. Therefore, the study of the existence of pesantren or institutions that gave birth to ulama is very important to be discussed. This is intended to measure the contribution of pesantren or other educational institutions in producing ulama.